Internet of Things-based home automation, energy management and smart security system - Bature, U. I.; Tahir, N. M.; Abubakar, A. K.; Makama, A. (Institute of Advanced Engineering and Science, 2021)
Objects can easily be remotely sensed, monitored and controlled when home is automated using the Internet of Things (IoT); this will give room for direct integration of the real world into computerized systems. Energy consumption is defined as the degree of the amount of power expended by a given load in an electric circuit. Nowadays, inefficient techniques used in monitoring and control of power consuming devices has contributed immensely in the high rate of power consumption in our homes, institutions, business places, and marketplaces. The design and implementation of an IoT-based home automation, energy management and smart security system has been proposed in this paper. The components used in the development of the system unit include an ESP8266 Wi-Fi component and the universal Arduino imbedded controller. The proposed scheme is aimed at assisting and supporting an efficient usage of power, and by doing so, power consumption as well as the risk of fire outbreaks will be greatly reduced to the barest minimal. The capability of remotely monitoring and controlling both electrical and electronic appliances via a web application is the main feature of the proposed scheme. The scheme provides better efficiency and accuracy as well as economic benefits.